Shoro shehreyar - Farah, Farukh (Book Group Karachi, 2005)
The Shoro Shehryar series is a collection of engaging Urdu children's books designed to stimulate young minds and foster a love for reading. These books feature captivating stories with vibrant illustrations, making learning fun and interactive.